A Mini Review of Antibacterial Properties of ZnO Nanoparticles - Gudkov, Sergey V.; Burmistrov, Dmitriy E.; Serov, Dmitriy A.; Rebezov, Maxim B.; Semenova, Anastasia A.; Lisitsyn, Andrey B. (Frontiers in Physics, 2021)
One of the promising ways to overcome microbial antibiotic resistance is the use of nanoparticles of metal oxides. As you know, a wide range of metals has antimicrobial action: Ag, Al, Cu, Fe, Mo, Mn, etc. The mechanisms of the antimicrobial action of metals are impaired functioning of microbial enzymes, generation of reactive oxygen species, damage to the cell membrane, and genotoxic action. ZnO nanoparticles have bacteriostatic and bactericidal action against gram-positive and gram-negative bacteria, as well as fungicidal activity. The mechanism of action is based on the release of Zn2+, generation of reactive oxygen species, damage to the cell membrane, binding to microbial proteins and nucleic acids. NPs based on ZnO have a number of advantages: high antibacterial efficiency at low concentrations (0.16-5.00 mM/l), action on a wide range of microbial strains, and relatively low production costs. Methods have now been found to improve the antimicrobial properties of nanoparticles. The use of several methods at the same time in some cases gives a synergistic effect. All of the above allows us to predict the use of ZnO nanoparticles as a new generation of antimicrobial agents in the near future.